Entrepreneurship in the sharing economy: a bibliographic perspective - Mitsu Feng, Cai; Park, Andrew; Montecchi, Matteo; Plangger, Kirk (Senate Hall, 2021)
The sharing economy has become an increasingly important concept for researchers and practitioners with the successes of Airbnb and Uber. Among all the studies of the sharing economy, research focusing on entrepreneurship only takes a small percentage and requires further development. As there have been few attempts at exploring the characteristics of and the relationships among the contributors and their publications in the field of research on the sharing economy and sharing economy entrepreneurship, this paper conducts a bibliometric analysis using VOSViewer software to identify the most prominent topics, works, authors, institutions and journals in these fields. Future research directions of entrepreneurship in the sharing economy are also investigated. This paper enables scholars and journal editors to better understand the current state of the academic conversation and to determine the potential areas to further develop in the field of entrepreneurship in the sharing economy.
Keywords: sharing economy|entrepreneurship|bibliometric analysis|